2008
DOI: 10.1080/00045600802098958
|View full text |Cite
|
Sign up to set email alerts
|

The Geographical Spread of Avian Influenza A (H5N1): Panzootic Transmission (December 2003–May 2006), Pandemic Potential, and Implications

Abstract: The World Health Organization (WHO) believes that the advent of highly pathogenic avian influenza A (H5N1) has moved the world closer to a further global pandemic of human influenza than at any time since the Hong Kong (H3N2) pandemic of [1968][1969]. The immediacy of the perceived threat is underscored by the current classification of the world at Phase 3 of WHO's operative six-phase system of pandemic alert, with H5N1 having met all the prerequisites for the onset of a human pandemic but one: the efficient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 72 publications
0
16
0
2
Order By: Relevance
“…Nascence of highly pathogenic forms of H5 and H7 or of other subtypes has never been observed in wild birds (Webster 1998). In addition, more than 90% of human H5N1 clusters have occurred among blood-related family members, suggesting possible genetic susceptibility (Smallman-Raynor and Cliff 2008;Abdel-Ghafar et al 2008). The current globalization of the poultry trade tends to homogenize the breeds used, resulting in homogeneity of existing genomes and day-old chicks globally, which may facilitate H5N1 spread among poultry.…”
Section: Poultry Productionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nascence of highly pathogenic forms of H5 and H7 or of other subtypes has never been observed in wild birds (Webster 1998). In addition, more than 90% of human H5N1 clusters have occurred among blood-related family members, suggesting possible genetic susceptibility (Smallman-Raynor and Cliff 2008;Abdel-Ghafar et al 2008). The current globalization of the poultry trade tends to homogenize the breeds used, resulting in homogeneity of existing genomes and day-old chicks globally, which may facilitate H5N1 spread among poultry.…”
Section: Poultry Productionmentioning
confidence: 98%
“…The global spread of H5N1 has been reviewed in details elsewhere (Li et al 2011;Smallman-Raynor and Cliff 2008;Webster and Govorkova 2006). Liang et al (2010) analysed historical occurrences of H5N1 and found that a 300-km spatial lag corresponded to the average distance between major residential centres, and a 1250-km spatial lag corresponded to important staging points of wild birds, while a 55-day time lag and 80-day time lag corresponded to poultry and wild birds, respectively.…”
Section: Transmission Patternmentioning
confidence: 99%
“…Several previous studies have used mapping to analyze the spread of epidemics by highlighting "spatial patterns". These include tuberculosis (Roth et al, 2016), cholera (Adesina, 1984;Ali et al, 2002), SARS-CoV (Lai et al, 2004;Shannon and Willoughby, 2004;Wang et al, 2008;Meade, 2014), MERS-CoV (Cotten et al, 2014), H1N1 influenza (Smallman-Raynor and Cliff, 2008;Souris et al, 2010), HIV (Wallace and Wallace, 1995;Wood et al, 2000) and dengue (Charette et al, 2017;Acharya et al, 2018;Atique et al, 2018;Zhu et al, 2019). In line with the approach of earlier studies, this paper attempts to analyze how the virus was transmitted across the globe and the underlying causes of its spread.…”
Section: Figure 1: Number Of Deaths Due To Covid-19 (7 Avril 2020)mentioning
confidence: 99%
“…For example, not taking into account the effects caused by geographical scale (the so-called “modifiable areal unit problem” [14]) could lead to interpretation errors when reviewing results from statistical analysis and modeling in area-based epidemiology. The predictive mapping of H5N1 risk in China, for instance, in Fang et al [15], conflicts with empirical observations [5], [16] and previous studies [17], [18]. Also, phylogenetic analysis [19] has its own limitations when genetic data are incomplete, and evolutionary models inappropriate [20].…”
Section: Introductionmentioning
confidence: 95%